Typification and taxonomical notes on the names published by Roberto de Visiani and Josif Pančić in Plantae Serbicae Rariores aut Novae—Decas II - Clementi, Moreno; Anačkov, Goran; Miola, Antonella; Vukojičić, Snežana (Phytotaxa, 2015)
We provide information on the typification of ten species names described by Roberto de Visiani and Josif Pančić in Plantae Serbicae Rariores aut Novae—Decas II, published in 1865, and one published by Pančić in Flora of the Principality of Serbia (1874). Ten lectotypes are designated here. The name Scabiosa achaeta Visiani & Pančić is synonymised with Scabiosa fumarioides Visiani & Pančić. Differential characters distinguishing Allium serbicum Visiani & Pančić and the similar A. pallens L. are given.